Relating Atlantic meridional deep-water transport to ocean bottom pressure variations as a target for satellite gravimetry missions - L. Shihora; T. Martin; A. C. Hans; R. Hummels; M. Schindelegger; H. Dobslaw (Ocean Science, 2025)
The Atlantic Meridional Overturning Circulation (AMOC) is a salient feature of the climate system that is observed with respect to its strength and variability using a wide range of offshore installations and expensive sea-going expeditions. Satellite-based measurements of mass changes in the Earth system, such as from the Gravity Recovery and Climate Experiment (GRACE) mission, may help monitor these transport variations at the large scale, by measuring associated changes in ocean bottom pressure (OBP) at the boundaries of the Atlantic remotely from space. However, as these signals are mainly confined to the continental slope and are small in magnitude, their detection using gravimetry will likely require specialised approaches. Here, we use the output of a fine-resolution (1/20<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="27pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="eb44dc7215fab272447585860bb94269"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="os-21-1533-2025-ie00001.svg" width="27pt" height="14pt" src="os-21-1533-2025-ie00001.png"/></svg:svg>°) regional ocean model to assess the connection between OBP signals at the western boundary of the North and South Atlantic to changes in the zonally integrated meridional deep-water transport. We find that transport anomalies in the ∼ 1–3 km depth range can be reconstructed using OBP variations spatially averaged over the continental slope, with correlations of 0.75 (0.72) for the North (South) Atlantic and root-mean-square errors of ∼ 1 Sv (sverdrup; 106 m3 s−1), on monthly to inter-annual timescales. We further create a synthetic data set containing OBP signals connected to meridional deep-water-transport anomalies; these data can be included in dedicated satellite gravimetry simulations to assess the AMOC detection capabilities of future mission scenarios and to develop specialised recovery strategies that are needed to track those weak signatures in the time-variable gravity field.